Different and Similar at the Same Time. Cultural Competence through the Leans of Healthcare Providers - Dell’Aversana, Giuseppina; Bruno, Andreina (Frontiers in Psychology, 2017)
Cultural competence (CC) for professionals and organizations has been recognized as a key strategy to reduce health care inequalities for migrants and to promote responsiveness to diversity. For decades its main aim has been matching health services to the cultural needs of migrant users. Otherwise literature highlighted the need to find a pragmatic middle way between the ‘static’ and the ‘dynamic’ views of culture that are recognizable in CC approaches. A pragmatic middle way to CC will be proposed as the way to respect diversity, even responding to cultural issues, without stereotyping or discriminating. To understand conditions that favor this pragmatic middle way this study aims to explore: (1) perceptions of healthcare providers in managing diversity; (2) strategies used to meet health needs at a professional and organizational level. A qualitative case study was conducted in a healthcare service renowned for its engagement in migrant sensitive care. Four different professional figures involved in CC strategies at different levels, both managerial and non-managerial, were interviewed. Data were analyzed using thematic analysis. Findings indicated that dealing with diversity poses challenges for healthcare providers, by confronting them with multilevel barriers to quality of care. A pragmatic middle way to CC seems to rely on complex understanding of the interaction between patients social conditions and the capacity of the institutional system to promote equity. Professional and organizational strategies, such as inter-professional and intersectional collaboration, cultural food adaptation and professional training can enhance quality of care, patient compliance responding to social and cultural needs.